2022
DOI: 10.1186/s40594-022-00379-3
|View full text |Cite
|
Sign up to set email alerts
|

Gendered patterns in students’ motivation profiles regarding iSTEM and STEM test scores: a cluster analysis

Abstract: Background Promoting and improving STEM education is being driven by economic concerns as modern economies have a rising demand for qualified researchers, technicians, and other STEM professionals. In addition, women remain under-represented in STEM-related fields, with significant economic and societal consequences. Abundant research has shown that gendered pathways into and away from STEM are mediated through motivation, but there is paucity of knowledge regarding gendered patterns in high sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Nevertheless, other factors, such as attitude, motivation, career plans, collaboration, confidence, self-efficacy, and stereotypes, may also influence interest. In addition to interest, motivation was found to be a behavioral factor that influenced the effort and achievement of girls in STEM fields, suggesting that motivation can be improved by incorporating long-term intervention measures to sustain girls' interest and efforts in STEM subjects [28], motivating girls to participate in real-life, place-based meaningful STEM subjects [158], promoting motivational links to university [67], and emphasizing motivational coexpression for teachers to motivate girls participation in STEM subjects [45]. Similarly, career plans influenced the aspirations and decisions of girls' participation in STEM fields; hence, some studies [47,127] have suggested that career plans can be improved by providing guidance and career counseling [151], and the implementation of relevant STEM camps [133].…”
Section: Behavioral Factors and Sdgmentioning
confidence: 99%
“…Nevertheless, other factors, such as attitude, motivation, career plans, collaboration, confidence, self-efficacy, and stereotypes, may also influence interest. In addition to interest, motivation was found to be a behavioral factor that influenced the effort and achievement of girls in STEM fields, suggesting that motivation can be improved by incorporating long-term intervention measures to sustain girls' interest and efforts in STEM subjects [28], motivating girls to participate in real-life, place-based meaningful STEM subjects [158], promoting motivational links to university [67], and emphasizing motivational coexpression for teachers to motivate girls participation in STEM subjects [45]. Similarly, career plans influenced the aspirations and decisions of girls' participation in STEM fields; hence, some studies [47,127] have suggested that career plans can be improved by providing guidance and career counseling [151], and the implementation of relevant STEM camps [133].…”
Section: Behavioral Factors and Sdgmentioning
confidence: 99%
“…One way to counteract these trends is to develop motivational STEM learning opportunities [19,20]. In their considerations on promoting motivation, Hite et al [21] (p. 3) assume that the age group from 11 to 14 years (middle school students) is an ideal period to promote motivation for STEM subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Generating a sufficient number of qualified professionals in science, technology, engineering and mathematic (STEM) areas is a matter of international concern (Thibaut et al, 2018a;Hernandez et al, 2014;Bøe, Henriksen, Lyons and Schreiner, 2011). Awareness of the problem with regard to young people's increasing reluctance to participate in STEM emerged in the early 1990s, and this has been a growing problem to this day (Bøe et al, 2011;Moore and Smith, 2014;Keith, 2018;Hermans et al, 2022;De Loof et al, 2022), as national reports continue to identify shortages of STEM graduates. The World Economic Forum (2016) predicted an increased demand for specialists in the STEM field for the years to come and stated that the pace of technology adoption is expected to remain unabated and may accelerate in some areas (World Economic Forum, 2020).…”
Section: Introductionmentioning
confidence: 99%